Hypoxemia in an adolescent: when the cause is between the lines - Pereira, Tatiana; Loureiro, Graça; Pereira, Sandra; Rocha, Cristina; Guimarães, Paulo; Oliveira, Sara (BIRTH AND GROWTH MEDICAL JOURNAL, 2020)
Spontaneous pneumomediastinum is a rare entity in pediatric age, with multifactorial etiology. A 16-year-old male with multiple allergies (mites, dogs, cats, and grasses), daily smoker (one pack/day for one year), and regular cannabis, cocaine, and amphetamine consumer went to the Emergency Department of the local hospital with cough, dyspnea, chest pain, and fever with 12 hours of evolution. On physical examination, the boy presented facies complaints, polypnea, shortness of breath, extensive subcutaneous emphysema in the cervical region and right hemithorax, and diminished vesicular murmur bilaterally with expiratory wheezing. Chest x-ray was performed, revealing alterations compatible with pneumomediastinum and subcutaneous emphysema in the cervical region. Urine test was positive for tetrahydrocannabinoids. Atopy (IgE levels) study was performed, with positive result, and serological testing was performed for Mycoplasma pneumoniae, showing IgM of 33U/mL and IgG of 25U/mL. In this clinical case, multiple pneumomediastinum triggering/predisposing factors can be identified, including marked smoking habits, acute mycoplasma infection, and inhaled and smoked drug consumption. The aim of this study was to review the pathophysiology/semiology of pneumomediastinum and emphasize the importance of clinical suspicion.